Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Certainly! Let's break down the given equation and solve for [tex]\( s \)[/tex] step-by-step.
1. Starting Equation:
[tex]\[ 2(-3s - 7) = -20 \][/tex]
2. Distribute the 2 across the terms inside the parentheses:
[tex]\[ 2 \cdot (-3s) + 2 \cdot (-7) = -20 \][/tex]
Simplifying this, we get:
[tex]\[ -6s - 14 = -20 \][/tex]
3. Isolate the [tex]\( -6s \)[/tex] term:
To do this, we need to get rid of the constant term on the left-hand side. Add 14 to both sides of the equation:
[tex]\[ -6s - 14 + 14 = -20 + 14 \][/tex]
Simplifying, we get:
[tex]\[ -6s = -6 \][/tex]
4. Solve for [tex]\( s \)[/tex]:
Divide both sides of the equation by [tex]\(-6\)[/tex]:
[tex]\[ s = \frac{-6}{-6} \][/tex]
Simplifying, we get:
[tex]\[ s = 1 \][/tex]
To summarize:
[tex]\[ \begin{tabular}{rl|l|} $2(-3 s-7)$ & $=-20$ & \\ $-6 s-14$ & $=-20$ & \\ $-6 s$ & $=-6$ & \\ $s$ & $=1$ & \\ & Add 14 to both sides. & \end{tabular} \][/tex]
Thus, the value of [tex]\( s \)[/tex] is [tex]\( 1 \)[/tex].
1. Starting Equation:
[tex]\[ 2(-3s - 7) = -20 \][/tex]
2. Distribute the 2 across the terms inside the parentheses:
[tex]\[ 2 \cdot (-3s) + 2 \cdot (-7) = -20 \][/tex]
Simplifying this, we get:
[tex]\[ -6s - 14 = -20 \][/tex]
3. Isolate the [tex]\( -6s \)[/tex] term:
To do this, we need to get rid of the constant term on the left-hand side. Add 14 to both sides of the equation:
[tex]\[ -6s - 14 + 14 = -20 + 14 \][/tex]
Simplifying, we get:
[tex]\[ -6s = -6 \][/tex]
4. Solve for [tex]\( s \)[/tex]:
Divide both sides of the equation by [tex]\(-6\)[/tex]:
[tex]\[ s = \frac{-6}{-6} \][/tex]
Simplifying, we get:
[tex]\[ s = 1 \][/tex]
To summarize:
[tex]\[ \begin{tabular}{rl|l|} $2(-3 s-7)$ & $=-20$ & \\ $-6 s-14$ & $=-20$ & \\ $-6 s$ & $=-6$ & \\ $s$ & $=1$ & \\ & Add 14 to both sides. & \end{tabular} \][/tex]
Thus, the value of [tex]\( s \)[/tex] is [tex]\( 1 \)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.